The Future of Botanical Monography: Report from an international workshop, 12–16 March 2012, Smolenice, Slovak Republic. Issue 1 (1st February 2013) - Marhold, Karol; Stuessy, Tod; Agababian, Mariam; Agosti, Donat; Alford, Mac H.; Crespo, Ana; Crisci, Jorge V.; Dorr, Laurence J.; Ferencová, Zuzana; Frodin, David; Geltman, Dmitry V.; Kilian, Norbert; et al.
Abstract: Monographs are fundamental for progress in systematic botany. They are the vehicles for circumscribing and naming taxa, determining distributions and ecology, assessing relationships for formal classification, and interpreting long–term and short–term dimensions of the evolutionary process. Despite their importance, fewer monographs are now being prepared by the newer generation of systematic botanists, who are understandably involved principally with DNA data and analysis, especially for answering phylogenetic, biogeographic, and population genetic questions. As monographs provide hypotheses regarding species boundaries and plant relationships, new insights in many plant groups are urgently needed. Increasing pressures on biodiversity, especially in tropical and developing regions of the world, emphasize this point. The results from a workshop (with 21 participants) reaffirm the central role that monographs play in systematic botany. But, rather than advocating abbreviated models for monographic products, we recommend a full presentation of relevant information. Electronic publication offers numerous means of illustration of taxa, habitats, characters, and statistical and phylogenetic analyses, which previously would have been prohibitively costly. Open Access and semantically enhanced linked electronic publications provide instant access to content from anywhere in the world, and at the same time link this content to all underlying data and digital resources used in the work. Resources in support of monography, especially databases and widely and easily accessible digital literature and specimens, are now more powerful than ever before, but interfacing and interoperability of databases are much needed. Priorities for new resources to be developed include an index of type collections and an online global chromosome database. Funding for sabbaticals for monographers to work uninterrupted on major projects is strongly encouraged. We recommend that doctoral students be assigned smaller genera, or natural portions of larger ones (subgenera, sections, etc.), to gain the necessary expertise for producing a monograph, including training in a broad array of data collection (e.g., morphology, anatomy, palynology, cytogenetics, DNA techniques, ecology, biogeography), data analysis (e.g., statistics, phylogenetics, models), and nomenclature. Training programs, supported by institutes, associations, and agencies, provide means for passing on procedures and perspectives of challenging botanical monography to the next generation of young systematists.